The communicative action pattern of appreciating and its realization in the text type ‘academic festschrift’ - Petkova-Kessanlis , Mikaela (Journal for German and Scandinavian Studies / Списание „Германистика и скандинавистика“, 2023)
The aim of this paper is to describe the realization of the complex communicative action pattern of appreciating in exemplars of the text type ‘academic festschrift’. First, speech and non-speech acts are identified that act as means of performing the communicative act of appreciation. Then, discourse and non-discourse acts of emphasis are recorded, which serve to construct or signal the reputation of the jubilarian. Since the text type ‘academic festschrift’ is controversial in the German-speaking scientific community, the paper also addresses the criticism of festschriften and its implications for the linguistic design of these publications. The study is a contribution to the field of text type research.